Squamata reptiles as a potential source of helminth infections when preyed on by companion animals - Mariaelisa Carbonara; Jairo Alfonso Mendoza-Roldan; Riccardo Paolo Lia; Giada Annoscia; Roberta Iatta; Antonio Varcasia; Giuseppe Conte; Giovanni Benelli; Domenico Otranto (Parasites & Vectors, 2023)
Abstract Background Squamate reptiles cohabiting with companion animals may represent a source of helminth infections, especially through predation by dogs and cats with an outdoor lifestyle. Methods In order to assess the role of reptiles as intermediate/paratenic hosts of trophically transmitted helminths, synanthropic reptiles (n = 245) captured from different ecological settings (i.e., households, dog shelters, urban, peri-urban and rural areas or natural parks) of southern Italy were examined for endoparasites. Parasitic cysts (i.e., larval forms of acanthocephalans, cestodes and nematodes) and free helminths (i.e., adult nematodes and digeneans) were morphologically and molecularly identified, and statistical analysis was carried out to evaluate the correlations between reptiles, infections, and ecological settings. Results Overall, 31% of reptiles were positive for at least one helminth, with Podarcis siculus (18.7%) and Tarentola mauritanica (8.1%) being the most frequently infected species. Among the parasites of medical interest, Joyeuxiella echinorhyncoides showed the highest prevalence (19.7%), followed by Diplopylidium acanthotetra (10.5%), Joyeuxiella pasqualei, Mesocestoides lineatus (5.6%) and Physaloptera sp. (3.9%). Macracanthorhynchus hirudinaceus was detected once. Podarcis siculus and T. mauritanica were associated with cestode infections. Conclusions The wide range of helminths detected here in reptiles living in sympatry with pets and the fact that many of these helminth species are parasitic and may infect companion animals (e.g., J. pasqualei, J. echinorhyncoides, D. acanthotetra, Physaloptera sp.) and humans (i.e., Macracanthorhynchus hirudinaceus, Mesocestoides lineatus) indicate the potential health risk associated with pets preying on these small vertebrates. Our results indicate the need for complementary investigations of trophically transmitted parasites in dogs and cats living in sympatry with reptiles. Graphical Abstract